2019
DOI: 10.1002/ejp.1435
|View full text |Cite
|
Sign up to set email alerts
|

Cornea nerve fibre state determines analgesic response to tapentadol in fibromyalgia patients without effective endogenous pain modulation

Abstract: Background Tapentadol is a centrally acting analgesic with μ‐agonistic activity combined with noradrenaline reuptake inhibition. Its mechanism of action relies on improvement of descending pain inhibition. In the current study, tapentadol's ability to enhance conditioned pain modulation (CPM, an experimental measure of descending pain inhibition) was evaluated in fibromyalgia patients with absent or reduced CPM responses. Methods A total of 34 fibromyalgia patients completed this double‐blind trial. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The magnitude of the CPM increase (about 20%) was in accordance with previously observed increases in patients with diabetic polyneuropathy and fibromyalgia syndrome. 13 , 29 In agreement with literature, 8 we did observe a significant analgesic effect with almost 50% of patients that experienced 50% of pain relief during treatment. In contrast to our previous studies, 13 , 29 we did not observe a correlation between analgesia and CPM% responses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The magnitude of the CPM increase (about 20%) was in accordance with previously observed increases in patients with diabetic polyneuropathy and fibromyalgia syndrome. 13 , 29 In agreement with literature, 8 we did observe a significant analgesic effect with almost 50% of patients that experienced 50% of pain relief during treatment. In contrast to our previous studies, 13 , 29 we did not observe a correlation between analgesia and CPM% responses.…”
Section: Discussionsupporting
confidence: 92%
“… 13 , 29 In agreement with literature, 8 we did observe a significant analgesic effect with almost 50% of patients that experienced 50% of pain relief during treatment. In contrast to our previous studies, 13 , 29 we did not observe a correlation between analgesia and CPM% responses. This might indicate that in patients with CLBP, pain relief is to a lesser extent or less consistently associated with CPM improvement and suggests a rather distinct mechanistic effect of tapentadol in different pain syndromes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Seven original trials were reported in 2 different publications each . Eleven trials (including 1203 participants) were not included in the quantitative analysis because outcome data were not reported and imputations were not possible or data indicated a skewed distribution …”
Section: Resultsmentioning
confidence: 99%
“…Occurrence of central sensitization is a sign of an increase in disease severity. Measurement of the endogenous pain modulatory system and sensory testing, in which a variety of stimuli and tests are applied to the skin, indicate that several phenotypes of neuropathic pain exist independent of the underlying disease [5][6][7].…”
Section: The Burden Of Neuropathic Painmentioning
confidence: 99%